2017
DOI: 10.24198/pjd.vol29no3.14469
|View full text |Cite
|
Sign up to set email alerts
|

Effect of black tea on the transverse strength of heat-polymerized acrylic resin

Abstract: Introduction: Heat-polymerized acrylic resin is the most basic denture material used. One of the mechanical properties of an acrylic resin is its transverse strength. The transverse strength test provides an overview of the material's durability in accepting the load at mastication. Consumption of tea, especially black tea in the world placed the second most consumed. The purpose of this study was to determine the effect of black tea on the transverse strength of heat-polymerized acrylic resin. Methods: This r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…3,6,14 In study by Kazanji et al solubility of soft-liner in artificial saliva was found to be increased after one month. 14 15 Safari et al tested the effect of 8% and 50% alcohol on hardness and tensile bond strength of soft-liner to the acrylic resin and found no significant interaction. 16 To the best of our knowledge, this is the first study reporting solubility of soft-liner and acrylic resin in tea with milk and green tea.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,6,14 In study by Kazanji et al solubility of soft-liner in artificial saliva was found to be increased after one month. 14 15 Safari et al tested the effect of 8% and 50% alcohol on hardness and tensile bond strength of soft-liner to the acrylic resin and found no significant interaction. 16 To the best of our knowledge, this is the first study reporting solubility of soft-liner and acrylic resin in tea with milk and green tea.…”
Section: Discussionmentioning
confidence: 99%
“…Phenol compounds being highly polar degrade the chemical bonds of acrylic resin and weakens the secondary polymeric chains and increases water absorption. 15 Tea with milk and green tea are commonly consumed drinks in India. Our in vitro study shows increased solubility of soft-liner and acrylic base resin when immersed in these solutions.…”
Section: Discussionmentioning
confidence: 99%
“…14 Good transverse strength, according to ADA specification No.12, is a minimum of 65 MPa. 15 The objective of this study is to analyze the role of Anonna muricata L. effervescent extract with various concentrations (25,35, and 45%) on the transversal strength of heat-cured acrylic resin.…”
Section: Introductionmentioning
confidence: 99%